Behind the hashtags: a review of Instagram posts on pediatric ADHD - Mahindrakar, Neha R.; Natarajan, Srutdi K.; Negi, Arundhati; Prajapati, Varshil; Rajput, Vrunda; Tabassum, Sameena; Sharma, Vansh (International Journal of Contemporary Pediatrics, 2025)
Social media has become an influential source of mental health information in recent years, raising concerns about the spread of misinformation. This study aimed to evaluate the reliability of Instagram posts related to pediatric attention-deficit/hyperactivity disorder (ADHD). A total of 761 posts were analyzed across 10 popular hashtags, with data collected on content relevance, type, gender representation, content creators, and engagement metrics such as likes, comments, and follower counts. Relevance was assessed using criteria from the DSM-5 and CDC guidelines. Only 31% of posts were found to be relevant to ADHD, with a majority being educational in nature. ADHD coaches were identified as the most frequent content creators. Gender representation in the posts represented females more than males. The overall engagement rate was calculated to be 16%. These findings highlight the widespread presence of potentially unreliable ADHD-related content on Instagram. Physicians must recognize the influence of such platforms on public health literacy and take proactive steps to counter misinformation, as it may contribute to misdiagnosis, inappropriate management, and confusion among patients and caregivers.